Faktor-Faktor yang Mempengaruhi Kemauan Membayar Pajak Wajib Pajak Orang Pribadi yang Melakukan Pekerjaan Bebas(Studi Empiris Pada Kantor Pelayanan Pajak Pratama Sukoharjo) - Murdiningtyas, Novia Erma, Drs. Suyatmin Waskito Adi, M.Si (2016)
This research was entitled "Factors Affecting the Willingness To Pay Tax Individual Tax Payers Are Doing Independent (Case Study at KPP Pratama sukoharjo)". This study was aimed to analyze the effect of taxpayer awareness, knowledge and understanding of tax regulations, perception of tax system affectivity, tax services quality, taxpayer percepyiom to the felt lease benefit, and the confidence level of the system administration and law on the willingness to pay tax individual tax payers are doing independent personal service in KPP Pratama Sukoharjo. The research was using survey quantitave research methods with questionnaire. The population was taxpayer which doing independent what elisted ini kpp pratama sukoharjo. Sampling was done by the methid of accidental sampling with 100 samples thas determined of slovin formula. Model of data analysis used in this study was a multiple linear regression analysis. Based on the research results get obtained that conducted, found the coefficient of determination (Adj. R2) OF 0.398. That means 39,8% of the willingness to pay taxes influenced by taxpayer awareness, knowledge and understanding of tax regulations, perception of tax system affectivity, tax services quality, taxpayer perception to the felt lease benefit, and the confidence level of the system administration and law. The independent variable in this study taxpayer awareness, knowledge and understanding of tax regulations, perception of tax system affectivity, tax services quality, taxpayer perception to the felt lease benefit, and the confidence level of the system administration and law had a significant influence on the willingness to pay tax individual tax payers are doing independent personal services (p < 0,05). Keyword : taxpayer awareness, knowledge and understanding of tax regulations, perception of tax system affectivity, tax services quality, taxpayer perception to the felt lease benefit, and the confidence level of the system administration and law, the willingness to pay tax individual tax payers are doing independent personal services.